A cloud platform for the development of resilient and intelligent services for the public sector - Krawczyk, Henryk; Orzechowski, Piotr; Wiszniewski, Bogdan (International Journal of Electronics and Telecommunications, 2026)
The ongoing progress of artificial intelligence enables the creation of advanced IT services in various areas of human activity. This paper examines the construction of intelligent cloud services for the analysis of digital documents used in the public sector. Examples of such services are provided. The use of a universal platform CAISE is proposed, which allows effective implementation of resilient and intelligent services. The general architecture of such a platform is presented, and their functionality is commented. Verification and validation elements of such platform are described in order to achieve the highest technological readiness level.